Trends in the incidence of presumed cardiac out-of-hospital cardiac arrest in Perth, Western Australia, 1997-2010 - Bray, J.; Di Palma, S.; Jacobs, Ian; Straney, L.; Finn, Judith (Elsevier, 2014)
Aim: This study investigated temporal trends in the incidence of out-of-hospital cardiac arrests (OHCA) in metropolitan Perth (Western Australia) between 1997 and 2010. Methods: We calculated crude and age-and-sex-standardised incidence rates (ASIRs) using the 2011 Australian population as the standard population. Incidence rates are reported per 100,000 population, and for eight age categories (0-14, 15-34, 35-64, 65-69, 70-74, 75-79, 80-84, =85). Temporal trends were analysed with linear regression. Results: Over the 14-years, 12,421 OHCAs of presumed cardiac aetiology were attended by St John Ambulance Western Australia paramedics. The overall ASIR per 100,000 population decreased significantly over this time (75.7-70.6, p < 0.001), but predominantly between 1997 and 2002 (75.7-65.9) and in those aged =65 years (410.2-336.7, p < 0.001). This trend was observed for both males and females and across all five-year age-groups between 65 and 84 years, but not in those =85 years - whom by 2010 represented 30% of the older adult (65+ years) OHCAs attended, up from 16% in 1997 (p < 0.001). Conclusions: Over the study period, a decline in the ASIR for OHCAs of presumed cardiac aetiology in Perth was observed. This is largely attributed to a decreasing incidence in the population aged 65-84 years between 1997 and 2002, and is likely the result of improvements in cardiovascular risk profiles that have previously been reported among Western Australian adults. Future studies of the impact of the ageing population are required.